Kepemimpinan Kepala Madrasah Dalam Peningkatan Mutu - Amril Mustofa (Proceedings of Annual Conference on Islamic Educational Management, 2021)
Leadership is one of the factors that determine the vision, mission and goals of an institution or organization. In the context of Islamic educational institutions, the components that become the driving force of this leadership are the principal, teachers, staff and all elements of education. In this paper, the authors explain what is the leadership and task of leaders in improving the quality of education, policies about leaders who use several factors such as knowledge, knowledge, challenges and interests. Therefore, it becomes interesting if this leadership is needed to make the basic values ​​of knowledge to increase deeper about leadership in improving quality in Islamic educational institutions.